Acute Neurological Deterioration in Large Vessel Occlusions and Mild Symptoms Managed Medically. Issue 5 (May 2020) - Saleem, Yasir; Nogueira, Raul G.; Rodrigues, Gabriel M.; Kim, Song; Sharashidze, Vera; Frankel, Michael; Al-Bayati, Alhamza; Bianchi, Nicolas; Haussen, Diogo C.
Abstract : Background and Purpose—: It is unclear which factors predict acute neurological deterioration in patients with large vessel occlusion and mild symptoms. We aim to evaluate the frequency, timing, and potential predictors of acute neurological deterioration ≥4 National Institutes of Health Stroke Scale (NIHSS) points in medically managed patients with large vessel occlusion and mild presentation. Methods—: Single-center retrospective study of patients with consecutive minor stroke (defined as NIHSS score of ⩽5 on presentation) and large vessel occlusion from January 2014 to December 2017. Primary outcome was acute neurological deterioration ≥4 NIHSS points during the hospitalization. Secondary outcomes included ΔNIHSS (defined as discharge minus admission NIHSS score). Results—: Among 1133 patients with acute minor strokes, 122 (10.6%) had visible occlusions on computed tomography angiography/magnetic resonance angiography. Twenty-four (19.7%) patients had ≥4 points deterioration on NIHSS at a median of 3.6 (1–16) hours from arrival. No clinical or radiological predictors of acute neurological deterioration ≥4 NIHSS points were observed on multivariable analysis. Rescue endovascular thrombectomy was performed more often in the ones with acute neurological deterioration ≥4 NIHSS points compared with patients with no deterioration (54% versus 0%; P <0.001). Acute neurological deterioration ≥4 NIHSS points was associated with ΔNIHSS ≥4 points (33% versus 4.9%; P <0.01) and a trend toward lower independence rates at discharge (50% versus 70%; P =0.06) compared with the group with no deterioration. In patients with any degree of neurological worsening, patients who underwent rescue thrombectomy were more likely to be independent at discharge (73% versus 38%; P =0.02) and to have a favorable ΔNIHSS (−2 [−3 to 0] versus 0 [−1 to 6]; P =0.05) compared with the ones not offered rescue thrombectomy. Conclusions—: Acute neurological deterioration ≥4 NIHSS points was observed in a fifth of patients with large vessel occlusion and mild symptoms, occurred very early in the hospital course, impacted functional outcomes, and could not be predicted by any of the studied clinical and radiological variables. Rescue thrombectomy was associated with improved clinical outcomes at discharge in patients with neurological deterioration. Abstract : Supplemental Digital Content is available in the text.